Nursing students’ appreciation of clinical supervision during work-integrated learning - Mphambanyeni J. Mugwari; Neltjie C. van Wyk; Ndivhaleni R. Lavhelani (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: Effective clinical supervision in learning-conducive environments is required to enhance students’ work-integrated learning. Conversely, ineffective clinical supervision can jeopardise students’ learning and skills development.